Strategic Writing: Multimedia Writing for Public Relations, Advertising and More - Charles Marsh; David W. Guth; Bonnie Poovey Short (Boston Short Solutions, 2008)
"Strategic Writing "emphasizes the strategic, goal-oriented mission of high-quality media and public relations writing with clear, concise instructions for more than 40 types of documents. This multidisciplinary text covers writing for public relations, advertising, sales and marketing, and business communication. Featuring a spiral binding, numerous examples and a user-friendly "recipe" approach, "Strategic Writing 2nd edition "is the ideal writing guide for public relations as well as for other disciplines.
Age Group: Adult
Includes index.
Keywords: Language; English Language; Business Report Writing -- Problems, Exercises, Etc; Business Writing -- Problems, Exercises, Etc; English Language -- Business English -- Problems, Exercises, Etc